Malaria burden and social determinants in Cameroon - Jude Tsafack Zefack; Fuanyi Awatboh; Brenda Mbouamba Yankam; Desmond Shu Che; Adanze Nge Cynthia; Odette Dzemo Kibu; Faustus Ajamah; Cynthia-Edith Ara-Nabangi Ndive; Patience Foumene Tiayah (Discover Public Health)
Abstract Introduction Malaria remains a significant public health concern in Cameroon, with high morbidity and mortality rates. Various factors, including socioeconomic factors, environmental conditions, and healthcare accessibility, contribute to disease transmission. Understanding these determinants is essential for effective control measures. Methods A scoping review was conducted following PRISMA guidelines. Studies and reports published between 2000 and 2024 focusing on social determinants of malaria disease in Cameroon were analyzed. Data extraction included study characteristics and key social determinants. Results A total of 86 studies were included. The key social determinants identified were education level, use of preventive measures, socioeconomic status, and access to healthcare. Malaria prevalence was highest in low-income populations, among the uneducated, and in regions with poor infrastructure. Additionally, seasonal and geographical variations also influence disease transmission. Conclusion Addressing malaria in Cameroon necessitates a multi-sectoral approach that integrates enhancements in education, healthcare accessibility, and environmental management. Additionally, policymakers should explore local funding strategies, including increased government investment in the health sector. Furthermore, future research should prioritize sustainable interventions aimed at mitigating malaria risk factors.